Grouper TRAF3 inhibits nodavirus infection by regulating the STING-mediated antiviral signaling pathway. Issue 123 (April 2022) - Wu, Siting; Sun, Mengshi; Zhang, Luhao; Kang, Shaozhu; Liao, Jiaming; Zhu, Zheng; Chen, Hong; Xu, Zhuqing; Xu, Linting; Zhang, Xin; Wei, Jingguang; Qin, Qiwei
Abstract: Tumor necrosis factor (TNF) receptor-associated factors (TRAFs) are major signal transducers for the TNF and interleukin-1/Toll-like receptor superfamilies that transduce signals from various immune receptors. To investigate the interaction of TRAF3 and other proteins in signaling pathways and to identify its antiviral function in teleosts, we cloned and characterized a TRAF3 homolog from orange-spotted grouper ( Epinephelus coioides ) (EcTRAF3). The open reading frame of EcTRAF3 consists of 1767 base pairs encoding a 588 amino acid protein, and the predicted molecular mass is 66.71 kDa EcTRAF3 shares 99.83% identity with TRAF3 of Epinephelus lanceolatus. Expression analysis revealed that EcTRAF3 was broadly distributed in examined tissues and was up-regulated under polyinosinic-polycytidylic acid and red-spotted grouper nervous necrosis virus (RGNNV) stimulation in vivo. EcTRAF3 was identified as a cytosolic protein based on fluorescence microscopy analysis. Overexpression of EcTRAF3 inhibited RGNNV replication in grouper spleen cells, and it interacted with the coat protein of RGNNV. Overexpression of EcTRAF3 also induced the activation of interferon β (IFN-β), IFN-stimulated response element (ISRE), and nuclear factor-κB (NF-κB). EcTRAF3 co-transfected with Stimulator of Interferon Genes (STING) of grouper (EcSTING) induced a significantly higher level of IFN-β promoter activity. Moreover, EcTRAF3 interacted with EcSTING, implying that EcTRAF3 may function as an enhancer in EcSTING-mediated signaling. Taken together, our results suggest that EcTRAF3 negatively regulates the RGNNV-induced cellular antiviral response and plays an important role in the immune response system of fish. Highlights: EcTRAF3 mRNA was broadly expressed in all examined tissues. EcTRAF3 were identified as a cytosolic protein. EcTRAF3 inhibited RGNNV replication in grouper spleen cells. EcTRAF3 interacted with EcSTING.